Perbedaan Orientasi Tujuan Berprestasi Belajar Pendidikan Jasmani antara Siswa Etnis Jawa dan Etnis Tionghoa - Dimyati Dimyati (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2003)
This research is aimed at knowing the goal orientation difference of learninf achievement in physical education between students having Javanese ethnic background and those having Tionghoa one. The population of this research were the SMU students in Yogyakarta City. The cluster random sampling technique was used by taking 320 students as the sample. The “TESQ” which developedby Duda & Nicholls (1989) was employed as the data collecting technique to reveal variabel, of the goal orientation of learning achievement in physical education.Then student demography data was used to reveal variabel of ethnic background. The calsulation result using T-test statistical analysis was t = -14.294 and p = 0.000. The result constituted the significant difference of the goal orientation of learning achievement in physical education between students having Javanese ethnic background and those having Tionghoa one. It means that the SMU students with Tionghoa ethnic background had higher goal orientation of learning achievement in physical education than those with Javanese ethnic background. Also, the students with Tionghoa background had higher goal orientation of learning achievement in physical education than those with Javanese ethnics background.Key Words : achievement, physical education, Javanese, Tionghoa